2012
DOI: 10.1111/j.1365-2702.2012.04341.x
|View full text |Cite
|
Sign up to set email alerts
|

Staff engagement as a target for managing work environments in psychiatric hospitals: implications for workforce stability and quality of care

Abstract: Leaders, nurse managers, clinicians as well as nurses themselves should be aware of the importance of work environments in mental healthcare facilities that favour engagement. Future efforts should focus on developing and sustaining practice environments that engage mental healthcare workers within interdisciplinary teams with the goal of creating a stable workforce possessing optimal possible knowledge, skills and abilities for delivering care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
93
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 56 publications
6
93
0
Order By: Relevance
“…A study showed that professionals working in hospitals had higher scores of depersonalization and nurses working in community services had a greater sense of personal fulfillment. (5)(6)(7)(8)(9)(10)(11)(12) The exposure to conflict situations and living with violence in the workplace can contribute to the psychological burden on nursing professionals. A protective measure against the violence of patients can be implemented by the service management with appropriate therapeutic support.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study showed that professionals working in hospitals had higher scores of depersonalization and nurses working in community services had a greater sense of personal fulfillment. (5)(6)(7)(8)(9)(10)(11)(12) The exposure to conflict situations and living with violence in the workplace can contribute to the psychological burden on nursing professionals. A protective measure against the violence of patients can be implemented by the service management with appropriate therapeutic support.…”
Section: Discussionmentioning
confidence: 99%
“…(18) The profile of the unit manager tends to influence the perception of work overload and emotional burnout of workers. (3,6,16) There is evidence that when the professional manages the unit jointly with the health team, other workers, patients and families, through meetings of the technical team, management board and assemblies with predetermined frequency, empowering all actors in the service, there is greater individual satisfaction of the nursing professionals with work, and lower perception of physical and mental burden of everyday labor. Hence the relevance of the unit manager having a good profile for the role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two-thirds used structural equation modelling to test the relationships between engagement and morale. The remainder used multiple regressions, except Van Bogaert et al, 208 who used multilevel/hierarchical linear modelling, as the individual was nested within the clinical unit. Only one was longitudinal in design.…”
Section: Measurement and Analysis Considerationsmentioning
confidence: 99%
“…Work engagement and a professional nursing practice environment have a positive correlation [15], and it is necessary to analyze the correlation between them at a unit level [16] [17]. Within the same workplace, it has been noted that the burnout of staff and managers shows a crossover reaction [18], and teamlevel burnout and work engagement are related to individual team members' burnout and work engagement [19].…”
Section: Introductionmentioning
confidence: 99%